Student Satisfaction with Learning Facilities and Infrastructure PJOK SMP Muhammadiyah 3 Ampel - Muhammad Nafian Nurhuda; Gatot Jariono (Kinestetik : Jurnal Ilmiah Pendidikan Jasmani, 2022)
Physical education aims to promote physical, mental, and emotional health. Facilities and infrastructure are needed to achieve the learning objectives of PJOK. That way the facilities and infrastructure can meet satisfaction with PJOK learning. There have been many studies conducted before regarding surveys of sports and health physical education learning facilities and infrastructure, but researchers want to examine the level of student satisfaction with sports and health physical education learning facilities and infrastructure that have not been researched much before. The purpose of this study was to see the level of student satisfaction with PJOK learning facilities and infrastructure at SMP Muhammadiyah 3 Ampel. Quantitative descriptive research method involving 60 students from all students at SMP Muhammadiyah 3 Ampel.  Data collection techniques use questionnaires, observations, and documentation. Analyze the data using the help of Microsoft Excel. The results of the study obtained, that the level of student satisfaction with the PJOK learning facilities and infrastructure at SMP Muhammadiyah 3 Ampel was included in the category of "Quite Satisfied", with some of the facilities and infrastructure owned by SMP Muhammadiyah 3 Ampel that were not adequate and the number of facilities that were still lacking. From the results of the research that has been carried out, it is hoped that it can provide benefits for the management of school facilities and infrastructure to increase student satisfaction with the facilities and infrastructure owned.